2019
DOI: 10.3390/vaccines7020050
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel Enhanced DNA Vaccine Vector for Preclinical Virus Vaccine Investigation

Abstract: DNA vaccines are stable, safe, and cost effective to produce and relatively quick and easy to manufacture. However, to date, DNA vaccines have shown relatively poor immunogenicity in humans despite promising preclinical results. Consequently, a number of different approaches have been investigated to improve the immunogenicity of DNA vaccines. These include the use of improved delivery methods, adjuvants, stronger promoters and enhancer elements to increase antigen expression, and codon optimization of the gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Protocols that involve utilizing specific protein components extracted from the pathogens to reduce risks and side -effects in the host produce 2 nd generation vaccines. By contrast 3 rd generation vaccines are vaccines derived from administration of genetically engineered DNA or mRNA to induce the host cells to produce an antigen in vivo, which in turn is expected to be recognized as non-self, and generate protective antibodies [5]. Here, we propose a new avenue in vaccinology: the generation of a molecule with the purpose of preventing infectious disease -that is, a vaccine -, but not based on the traditional norms of antigen-idiotype binding.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols that involve utilizing specific protein components extracted from the pathogens to reduce risks and side -effects in the host produce 2 nd generation vaccines. By contrast 3 rd generation vaccines are vaccines derived from administration of genetically engineered DNA or mRNA to induce the host cells to produce an antigen in vivo, which in turn is expected to be recognized as non-self, and generate protective antibodies [5]. Here, we propose a new avenue in vaccinology: the generation of a molecule with the purpose of preventing infectious disease -that is, a vaccine -, but not based on the traditional norms of antigen-idiotype binding.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to assess the immunogenicity of a multivalent HIV vaccine including DNA vector alone or in combination with Env glycoprotein (gp120), it was found that the coadministration of gp120 Env protein components with DNA vaccine leads to early and potent induction of Env V1/V2 IgG binding antibody responses [38]. It was also recently reported that a short DNA vaccine vector (of 172 bp length) derived from the porcine circovirus PCV-1 capsid protein promoter, and expressing various HIV-1 subtypes, leads to high immunogenicity of the HIV-1 subtype C candidate DNA vaccines in rodents, at up to 10-fold lower doses than usually used [39].…”
Section: Hiv Vaccine Candidates and Antibodies Expressed In Plantsmentioning
confidence: 98%
“…Once inserted into host cells, the cellular machinery will express the antigens encoded by the DNA and an immune response will be elicited. Some advantages of DNA vaccines include the safe administration to immunocompromised individuals compared to MLVs, the potential for combining multiple plasmids for a broad-spectrum combination vaccine, and the ease of engineering compared to classical vaccines (31)(32)(33). Along with these advantages DNA vaccines induce both humoral and cell mediated responses, and function as pathogen associated molecular patterns (PAMPS) attenuating the necessity for adjuvant (32,34,35).…”
Section: Introductionmentioning
confidence: 99%